The Influence of Room Occupancy and Average Daily Rate on the Revenue Per Occupied Room of Hotel X - Rachellia Dharsana; I Putu Arnawa; Ni Luh Riska Yusmarisa (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
Revenue per occupied room reflects hotel’s financial performance. Revenue per occupied room is affected by several factors two of them are occupancy rates and average room rates. The revenue per occupied room in hotel x has increased in the past three years but fluctuates every month. This research was conducted to determine the influence of room occupancy and average daily rate on the revenue per occupied room of hotel x. The data collection methods used in this research are interviews, documentation and library studies. The data used in this research is data in 2021-2023. The method of data analysis used in this research were multiple linear which assisted by SPSS series 25 program. The results of this research showed that partially and simultaneously the room occupancy and average daily rate had a positive and significant impact on the hotel's revenue per occupied room. The coefficient determination test showed room occupancy and average room rate had 90,2 per cent influence on hotel’s revenue per occupied room, with the remaining 9,8 per cent being explained by the other variable that was not used in this research.